Identification of Central Nervous System Complications Related To Eclampsia (Bangladesh Journal of Neuroscience, 2014)
Background: Eclampsia is a complex hypertensive disorder of pregnancy affecting multiple systems. Central nervous system is commonly affected and is a cause of significant morbidity and mortality in women. Various neurological complications are found in eclamptic patients.Aims and Objectives: The aim of this study was to explore the various CNS complications related to eclampsia.Materials and Methods: This retrospective observational study was carried out in the ‘Eclampsia ward’ of Department of Gynaecology and Obstetrics of Dhaka Medical College Hospital (DMCH), during the period of November, 2010 to October, 2011 in patients admitted with a history of eclampsia. Fifty(50) patients were included in this study. Data was collected by a semistructured questionnaire. The patients were interviewed and a complete clinical examination was performed by the investigator. It was reviewed by a consultant neurologist.Results & conclusion: The results revealed that patients had headache, comatose state, stroke, focal neurological deficit, post partum psychosis, aphasia and cortical blindness. Death occurred in 6.0% of patients. As eclampsia is the third major cause of pregnancy related maternal death in Bangladesh (16%), and no study has yet not been reported in this field, this study might help in formulating management plan; predict prognosis and functional recovery in the individual cases.Bangladesh Journal of Neuroscience 2014; Vol. 30 (1): 11-15